Simulation Study on Variants of ABS - Ashok Kumar, Srinivaas; Thirumalini, S; Mohankumar, P; Ram Sundar, R; Aravind, C (International Journal of Engineering and Technology, 2018)
The performance characteristics of different variants of Anti-Lock Braking System (ABS) in a normal passenger car is investigated. ABS prevent lock-up of wheels and maintains steer ability of the vehicle during braking. Vehicle stopping distance, brake pressure, wheel slip and slide-slip are made using Simulink software and system study was conducted an investigation is done. The variants of ABS taken for the study are 2-channel ABS (front wheels), Cross-ABS (alternate wheels: front left and rear right) and full (four channel) ABS. The Simulink model was interfaced with IPG Carmaker and simulation was performed to include the aerodynamics, tire friction and road friction. The results of the simulation were validated to obtain conclusions on the braking performance for different variants of ABS.Â